Dystocia and stillbirth in beef cattle with subclinical hypomagnesemia: a case study - Sosa, Emiliano; Miqueo, Evangelina; Mejía, M.; Fernandez, Eduardo Luján; Fernandez Tovo, Martina Elizabeth; Cruz, M.; Campero, Lucia Maria; Moore, Prando Dadin; Morrell, Eleonora Lidia; Canton, German Jose (Facultad de Ciencias Veterinarias, Universidad Nacional del Nordeste, 2025)
We describe the occurrence of dystocia and stillbirths in Brangus and Aberdeen Angus cows and heifers within the context of mineral deficiencies in a beef farm located in Buenos Aires province, Argentina. Water, forage, and blood samples were collected for chemical, serology, and mineral quantification, respectively. Birth weight, sex and presentation of calves were monitored at birth, and calving ease was evaluated. A stillborn Aberdeen Angus female was examined postmortem. The occurrence of dystocia and subsequent stillbirths was recorded in 6.11% (32 out of 523) of dams with subclinical hypomagnesemia. During calving, dystocic animals exhibited prolonged labor, stillbirths, and delivery assistance. No difference in birth weight was registered between dystocic and eutocic births. A postmortem examination of a stillborn calf revealed low hepatic copper concentrations and congenital Neospora caninum infection. However, no histopathological findings consistent with N. caninum infection were observed, confirming only the congenital infection. Maternal hematological analyses indicated suboptimal levels of calcium, magnesium, and copper. Mineral supplementation with MgCl2 + MgO reduced the likelihood of dystocic calvings in cows. Additionally, noninfectious causes of perinatal deaths were serologically identified in the dams. Dietary analysis showed no mineral-interfering factors. While dystocia is common, its association with mineral deficiencies is likely underreported. Further research is needed to better understand and mitigate the negative impact of mineral deficiencies on the sustainability of beef production systems in the región.